(3GdJMdjd Gdcej aj eLGd GdCYeGd (B:s (3CSGSjGJ Yde GdEOGQI GdJWHjbj (B/s - (3eQSi, fHjd eMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2004)
(3ebOeI aj Yde GdEOGQI, JMdjd GdbQGQGJ ,fXQjI GdeHGQGI ,GdHQeLI GdNWjI ,CSdhH GdMd GdHjGfj hCSdhH GdSejdcj ,JMdjd GdMSGHjI hGdKfGFjI,GdfeGPL GdTHcjI,HQeLI GdCgOGa,GOGQI GdeTQhYGJ ,GdJfHD HGdWH,feL LOhdI GdCYeGd ,CSdhH Gdfbd , feGPL Uaha GdGfJXGQs
(3GdeQGLY U(B.410s
Keywords: (3GJNGP GdbQGQs; (3EOGQI GdHQeLI GdNWjIs; (3GdJMdjd Gdcejs